2013
DOI: 10.1371/journal.pone.0067637
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TRPC Channels in Lung Cancer Cell Differentiation and the Correlation Analysis in Human Non-Small Cell Lung Cancer

Abstract: The canonical transient receptor potential (TRPC) channels are Ca2+-permeable cationic channels controlling the Ca2+ influx evoked by G protein-coupled receptor activation and/or by Ca2+ store depletion. Here we investigate the involvement of TRPCs in the cell differentiation of lung cancer. The expression of TRPCs and the correlation to cancer differentiation grade in non-small cell lung cancer (NSCLC) were analyzed by real-time PCR and immunostaining using tissue microarrays from 28 patient lung cancer sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 47 publications
5
55
0
Order By: Relevance
“…Accordingly, these changes could represent the most critical events underlying Ca 2ϩ remodeling and acquisition of cancer features. In support of this view, it has been reported that TRPC channels are overexpressed and regulate cell proliferation in human nonsmall cell lung, breast, liver, stomach, and glioma cancer (13,(51)(52)(53)(54) eration of tumor cells because one of its physiological roles is the modulation of the cell cycle progression through the regulation of cell volume (56). In addition, it has been reported recently that the interaction between STIM1 and TRPC1 is essential for cell migration after wounding in rat intestinal, epithelial cells (57).…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, these changes could represent the most critical events underlying Ca 2ϩ remodeling and acquisition of cancer features. In support of this view, it has been reported that TRPC channels are overexpressed and regulate cell proliferation in human nonsmall cell lung, breast, liver, stomach, and glioma cancer (13,(51)(52)(53)(54) eration of tumor cells because one of its physiological roles is the modulation of the cell cycle progression through the regulation of cell volume (56). In addition, it has been reported recently that the interaction between STIM1 and TRPC1 is essential for cell migration after wounding in rat intestinal, epithelial cells (57).…”
Section: Discussionmentioning
confidence: 82%
“…Among the TRPC subfamily, the expression of TRPC1, TRPC3, TRPC4, and TRPC6 was correlated with differentiation grades in NSCLC [64]. The same study reported that the inhibition of TRPC channels decreased cell mitosis, by using the pore-blocking antibodies T1E3 and T367E3 to inhibit specifically TRPC1 and TRPC3/6 in A549 cells.…”
Section: Calcium Channels Proliferation and Lung Cancermentioning
confidence: 85%
“…We have also showed that the decrease of the extracellular Ca 2+ concentration [Ca 2+ ] o inhibits MCF-7 cell proliferation suggesting that Ca 2+ influx is essential for BC MCF-7 cell proliferation [40]. TRPC1 is an important Ca 2+ regulator in a variety of cell types including malignant gliomas [41], ovarian cancer [42], and lung cancer [43, 44]. In the MCF-7 breast cancer cell line, we previously demonstrated that TRPC1 provides a Ca 2+ entry that regulates cell proliferation via ERK1/2 phosphorylation [16].…”
Section: Discussionmentioning
confidence: 99%